Rheumatoid arthritis: problems of treatment at the present stage - N. V. Chichasova (Современная ревматология, 2018)
The possibilities of rheumatoid arthritis therapy have been significantly expanded today. In addition to conventional synthetic disease-modifying antirheumatic drugs (csDMARDs), biologic agents (BAs), and a targeted synthetic DMARD, a control treatment strategy has been put into practice.The paper demonstrates successes in the early prescription of csDMARD and the implementation of treat-to-target principles – to achieve the goal after 6 months in 50% of patients receiving subcutaneous methotrexate and 45% of those using a Leflunomide generic. During this therapy, there is a lower need for BAs and targeted synthetic DMARDs. The priority problem is to train general practitioners in methods for the early detection of RA and to set up schools for these patients.